1987
DOI: 10.1111/j.1365-2141.1987.tb04141.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of three permanent human leukaemia cell lines producing immunoreactive calcitonin

Abstract: Three permanent human leukaemia cell lines, designated EW2, LG3 and MS6, were established from bone marrow aspirates of a patient with acute myelomonocytic leukaemia (EW2), acute monocytic leukaemia (LG3) and acute myeloblastic leukaemia (MS 6). In vitro all lines exhibited a myelomonocytoid marker profile in terms of classical staining reactions and cell-surface antigen structure. In supernatants and extracts of EW2 and MS 6 cells immunoreactive human calcitonin was found in raised levels. No significant leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 11 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…Results of previous studies [23] demonstrated that immunoreactive h-CT in sera and cell extracts of individual patients exhibited molecular weights ranging from 3500 to 60000 daltons. The normal low molecular weight fraction (3500 d) was found beside high molecular h-CT only in sera of patients, whereas in cell extracts of leukaemia blast from patients [23] and leukaemic cell lines [16], only high molecular weight forms of immunoreactive CT were present. These findings, and the in-vitro production of h-CT by leukaemic cells, strongly suggest that elevated serum levels of h-CT in patients with leukaemia originate from the leukaemic cells rather than from other sources including non-malignant and physiological states.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Results of previous studies [23] demonstrated that immunoreactive h-CT in sera and cell extracts of individual patients exhibited molecular weights ranging from 3500 to 60000 daltons. The normal low molecular weight fraction (3500 d) was found beside high molecular h-CT only in sera of patients, whereas in cell extracts of leukaemia blast from patients [23] and leukaemic cell lines [16], only high molecular weight forms of immunoreactive CT were present. These findings, and the in-vitro production of h-CT by leukaemic cells, strongly suggest that elevated serum levels of h-CT in patients with leukaemia originate from the leukaemic cells rather than from other sources including non-malignant and physiological states.…”
Section: Discussionmentioning
confidence: 92%
“…The present investigation shows no significant coincidence of these two hormones. Of 52 patients, only 16 exhibited elevated levels of both peptides, 14 had normal levels for both hormones and 21 showed high serum levels of one compound only. This distribution indicates that the pathway of alternative RNA splicing also occurs in leukaemic blasts producing CT gene-related peptides 'ectopically'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for binding sites, the storage and/or synthesis of neuropeptide(s) seem(s) to occur mostly in iymphocytes but, to our knowledge, nothing has been described for substance P or bombesin in contrast with descriptions for ACTH [19,48,62,69,70], preproenkephalin [87] or calcitonin [35]. On the other hand, bombesin was identified in alveolar macrophages by HPLC, RIA and immunofluorescence without any cross-reactivity with substance P [85].…”
Section: Relationships Between Neuropeptides and Blood Or Connective mentioning
confidence: 99%